2022
DOI: 10.1108/jarhe-03-2022-0082
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the public higher education institution (PHEI) acceptance of online meetings applications during COVID-19 pandemic: an empirical study

Abstract: PurposeIn order to ensure effectiveness of staff's performance using online meetings applications during coronavirus disease (COVID-19), having the behavioural intention is mandatory for staff to measure, test, and manage the staff's data. Understanding of Public Higher Education Institution (PHEI) staffs' intention and behaviour toward online meetings platforms is needed to develop and implement effective and efficient strategies. The objectives of this paper to identify the factors that affect staff to use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…Similarly, the study found a significant positive effect of the perceived usefulness and ease of use of these tools on employees' intention to use them. These results are consistent with studies [39,40] in the literature using online meeting tools.…”
Section: Theoretical Contributionssupporting
confidence: 92%
See 4 more Smart Citations
“…Similarly, the study found a significant positive effect of the perceived usefulness and ease of use of these tools on employees' intention to use them. These results are consistent with studies [39,40] in the literature using online meeting tools.…”
Section: Theoretical Contributionssupporting
confidence: 92%
“…The desire of students to use web-based video conferencing for learning is influenced by factors such as ease of use, usefulness, and complexity [60]. Individuals who perceive online meeting tools as advantageous and straightforward may possess a favorable attitude towards this technology and, consequently, are inclined to use it even after the pandemic ends [38][39][40]. As users master online meeting platforms and recognize their utility, they develop favorable attitudes towards these platforms and intend to use them extensively.…”
Section: H3 Expectations Have a Direct Positive Impact On The Intenti...mentioning
confidence: 99%
See 3 more Smart Citations